In Dubio Pro Natura: in Doubt, should the Environment Be a Priority? A Discourse of Environmental Justice in Indonesia - Arifin, Ridwan; Idris, Siti Hafsyah (Faculty of Law, Jambi University, 2023)
This study explores the critical question of whether the environment should be prioritized in situations of uncertainty, encapsulated by the Latin phrase “In Dubio Pro Natura” (In Doubt, For Nature). Focusing on the context of Indonesia, the discourse navigates the complex terrain of environmental justice. The study delves into the multifaceted challenges faced by Indonesia, considering economic development, social equity, and ecological sustainability. By examining cases of environmental degradation, resource exploitation, and their societal implications, the study aims to shed light on the ethical dimensions of decision-making in the face of environmental uncertainties. Drawing on diverse perspectives, including indigenous knowledge and international frameworks, the discourse advocates for a nuanced approach that balances economic growth with environmental stewardship and social justice. Ultimately, this study outlines the necessity of reevaluating priorities, fostering sustainable practices, and ensuring equitable environmental policies for the well-being of present and future generations in Indonesia.